PENGARUH LAYANAN KOPERASI DIGITAL TERHADAP PERILAKU KONSUMTIF STAF CU KELING KUMANG AREA SINTANG SATU DENGAN KEMUDAHAN TRANSAKSI SEBAGAI VARIABEL MEDIASI - Opralsen Gurning; Darius Damestuteles; Fitria Elvi (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2025)
This research is motivated by the phenomenon of increasing consumptive behavior of Savings and Loans Cooperative staff at CU Keling Kumang Sintang Satu Area, along with the presence of digitalization services in the form of the Keling Kumang Digital application. The purpose of this study is to analyze the effect of digital cooperative services on the consumer behavior of staff at CU Keling Kumang Area Sintang I, both directly and through transaction convenience as a mediating variable. The method used is quantitative, with regression and path analysis techniques. Data were obtained from 106 respondents through questionnaires. The results show that digital cooperative services have a significant direct effect on consumer behavior (tvalue 3.264 > t-table 1.983; significance 0.01 < 0.05) with a correlation coefficient of 0.304. Transaction convenience also has a positive and significant effect on consumer behavior (tvalue 3.769; significance 0.000) with a beta coefficient of 0.348. However, the indirect effect of digital cooperative services on consumer behavior through transaction convenience is not significant (coefficient -0.114; significance 0.659), although full mediation occurs as the direct effect becomes insignificant. Other findings indicate that factors such as financial literacy, lifestyle, and social influence also affect consumer behavior. The conclusion of this study is that cooperative digitalization plays a role in increasing staff consumption, but it must be balanced with financial literacy education to prevent excessive consumption. Key words: digital cooperative services, transaction convenience, consumer behavior